“Prevalencia de mycoplasma hyopneumoniae en porcinos de traspatio en el cantón Latacunga, provincia de Cotopaxi” - Arcos Reyes, Emily Cristina (2023)
Mycoplasma hyopneumoniae is one of the pathogens responsible for respiratory diseases in pigs, contributing to the Porcine Respiratory Disease Complex and the Porcine Reproductive and Respiratory Syndrome; it is a disease of high dissemination because of its clinical and subclinical manifestations. The objective of this research was to determine the prevalence of Mycoplasma hyopneumoniae in backyard pigs in Latacunga, city of Cotopaxi province. The blood serum of 150 randomly selected pigs, distributed in the 10 rural parishes of the city, it was analyzed using the competitive ELISA test. The prevalence was calculated and the chi-square test was used as a statistical tool to determine the dependence of the variables. As a result, a prevalence of 16.67% was obtained, with the Tanicuchi parish with the highest percentage of 24%, Poaló with 20%, Once de Noviembre and Pastocalle with 16%, Guaytacama with 12%, Joseguango Bajo with 8%, Alaquez with 4%, for Toacaso, Mulaló and Belisario Quevedo there were no positive cases. Variables in research such as age and sex showed that there is no dependence for the disease. The epidemiological map allowed observing the geographical areas in which there are positive cases.